Technology park services: The impact on incubating companies - Abidin, Rahimi; Hasnan, Norlena; Osman, Nor Hasni; Abdullah, Che Sobry; Mohtar, Shahimi (IBIMA Publishing, 2014)
The development of technology parks in Malaysia creates the expectations that they will contribute significantly to the industrialization. Therefore, there is increasing number of research conducted on technology parks performance.However, there is still uncertainty about whether technology parks are achieving their goals or not and exactly what their impact is on their tenants.To contribute to understanding this issue, this paper focuses specifically on the impact of technology park services on high technology industries. A case study on one of the well-established technology parks in Malaysia that is Kulim Hi-Tech Park (KHTP) has been conducted.After a series of interviews with the administrator and review of literature, nine evaluation criteria were identified and used to observe the impact of technology park services on the industrial tenants of the technology park.From a survey on the industrial tenants in KHTP, it is found that the technology park has all the nine evaluated criteria However, these criteria have different categories of impact on the tenants.It can be concluded that there is still more room to improve in ensuring the competitiveness of the technology park. This study could be extended to other technology parks in the whole country.